Cooling-off in negotiations: does it work? - Oechssler, Joerg; Roider, Andreas; Schmitz, Patrick W. (Discussion paper series, 2008)
Negotiations frequently end in conflict after one party rejects a final offer. In a large-scale internet experiment, we investigate whether a 24-hour cooling-off period leads to fewer rejections in ultimatum bargaining. We conduct a standard cash treatment and a lottery treatment, where subjects receive lottery tickets for several large prizes - emulating a high-stakes environment. In the lottery treatment, unfair offers are less frequently rejected, and cooling-off significantly reduces the rejection rate further. In the cash treatment, rejections are more frequent and remain so after cooling-off. This treatment difference is particularly pronounced for subjects with lower cognitive abilities.